Female hyperandrogenism and elite sport - Lindén Hirschberg, A. (Endocrine Abstracts, 2019)
Androgens are considered beneficial for athletic performance by potent anabolic effects on muscle mass and bone tissue. Testosterone also increases circulating hemoglobin, which will enhance oxygen uptake. Furthermore, androgens may exert behavioral and psychological effects of importance for athletic performance including increased mental drive and competitiveness. Studies in men have shown clear relationships with both exogenous and endogenous circulating testosterone to muscle mass, strength and hemoglobin. Corresponding evidence in women is much more limited. However, recent studies have demonstrated associations between circulating testosterone in the normal female range and muscle mass and strength, respectively. Moreover, it has been demonstrated that women with polycystic ovary syndrome (PCOS) are overrepresented in elite athletes. PCOS, which is a mild form of hyperandrogenism, is associated with an anabolic body composition including more muscle mass than in non-PCOS women. There are data to support that PCOS is advantageous for physical performance. This condition could therefore play a role in the recruitment of women to competitive sports. The prevalence of differences of sex development (DSD) is also increased among female athletes. XYDSD may cause a greatly increased production of testosterone in the male range, i.e. 10-20 times higher than in the normal female range. If the individual has normal androgen sensitivity, her muscle mass will develop as in males, along with increasing signs of virilization. Since sports are divided into female and male classification, it could be considered unfair to allow female athletes with endogenous testosterone in the male range to compete against women with normal female androgen levels. This lead the International Association of Athletics Federation and the International Olympic Committee to establish regulations for management of hyperandrogenism in female athletes. However, the regulations are controversial, and have been challenged. Ultimately, it is a question of ensuring fair and meaningful competition in women`s sport.